Decoding serotonin: the molecular symphony behind depression - Shu, Yue; Tian, Lei; Wang, Xing; Meng, Tinyang; Yu, Shouyang; Li, Yulan (Frontiers in Cellular Neuroscience, 2025)
The serotonin (5-hydroxytryptamine) system represents a crucial neurotransmitter network that regulates mood, behavior, and cognitive functions, playing a significant role in the pathogenesis and progression of depression. Although this perspective faces significant challenges, the serotonin system continues to exert substantial modulatory effects on specific aspects of psychological functioning and actively contributes to multiple pathological processes in depression development. Therefore, this review systematically integrates interdisciplinary research advances regarding the relationship between the 5-hydroxytryptamine (5-HT) system and depression. By focusing on core biological processes including serotonin biosynthesis and metabolism, SERT gene regulatory networks, and protein molecular modifications, it aims to elucidate how 5-HT system dysregulation contributes to the development of depression, while providing novel research perspectives and therapeutic targets for innovative antidepressant drug development.